Peroxo-iron and oxenoid-iron species as alternative oxygenating agents in cytochrome P450-catalyzed reactions: switching by threonine-302 to alanine mutagenesis of cytochrome P450 2B4. - Vaz, A D (1996)
Among biological catalysts, cytochrome P450 is unmatched in its multiplicity of isoforms, inducers, substrates, and types of chemical reactions catalyzed. In the present study, evidence is given that this versatility extends to the nature of the active oxidant. Although mechanistic evidence from several laboratories points to a hypervalent iron-oxenoid species in P450-catalyzed oxygenation reactions, Akhtar and colleagues [Akhtar, M., Calder, M. R., Corina, D. L. & Wright, J. N. (1982) Biochem. J. 201, 569-580] proposed that in steroid deformylation effected by P450 aromatase an iron-peroxo species is involved. We have shown more recently that purified liver microsomal P450 cytochromes, including phenobarbital-induced P450 2B4, catalyze the analogous deformylation of a series of xenobiotic aldehydes with olefin formation. The investigation presented here on the effect of site-directed mutagenesis of threonine-302 to alanine on the activities of recombinant P450 2B4 with N-terminal amino acids 2-27 deleted [2B4 (delta2-27)] makes use of evidence from other laboratories that the corresponding mutation in bacterial P450s interferes with the activation of dioxygen to the oxenoid species by blocking proton delivery to the active site. The rates of NADPH oxidation, hydrogen peroxide production, and product formation from four substrates, including formaldehyde from benzphetamine N-demethylation, acetophenone from 1-phenylethanol oxidation, cyclohexanol from cyclohexane hydroxylation, and cyclohexene from cyclohexane carboxaldehyde deformylation, were determined with P450s 2B4, 2B4 (delta2-27), and 2B4 (delta2-27) T302A. Replacement of the threonine residue in the truncated cytochrome gave a 1.6- to 2.5-fold increase in peroxide formation in the presence of a substrate, but resulted in decreased product formation from benzphetamine (9-fold), cyclohexane (4-fold), and 1-phenylethanol (2-fold). In sharp contrast, the deformylation of cyclohexane carboxaldehyde by the T302A mutant was increased about 10-fold. On the basis of these findings and our previous evidence that aldehyde deformylation is supported by added H202, but not by artificial oxidants, we conclude that the iron-peroxy species is the direct oxygen donor. It remains to be established which of the many other oxidative reactions involving P450 utilize this species and the extent to which peroxo-iron and oxenoid-iron function as alternative oxygenating agents with the numerous isoforms of this versatile catalyst.